Procedência da cocaína e maconha definida por isótopos estáveis - Buschini, Renata Luci [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Objectives: the aim of this work was to define the range of possible values for each isotope of carbon-13 and nitrogen-15 for cocaine and marijuana seized in Botucatu-SP, with the intention of distinguishing the geographical origin of the drug. Materials and Methods: samples of marijuana and cocaine were collected at the time of incineration. Then, at the Stable Isotope Center from São Paulo State University in Botucatu, São Paulo, Brazil, samples of marijuana were subjected to the drying process and subsequent grinding. Samples of cocaine were not submitted to the processes of drying and grinding because they were already in adequate granulometry. Subsequently, the samples of both drugs were weighed in accordance with the standards for carbon-13 and nitrogen-15. Lastly, CO2 and N2 gases were obtained from the samples through the elemental analyzer. They were then analyzed in a mass spectrometer to obtain values of δ13C and δ15N in ‰. Results and Discussion: the results of marijuana allowed for comparison with regions of Queensland, Australia, according to the range of δ13C between -29.9 ‰ and -29.3 ‰ and δ15N range from 4.1 ‰ to 5.8 ‰. The results were also consistent with those of the state of Pará, Brazil, where the values of δ13C and δ15N were -30.3 ± 0.7 ‰ and 5.0 ± 1.3 ‰, respectively. Also the results were in accordance with those from the state of Mato Grosso do Sul, Brazil, in which δ13C values varied by -28.7 ± 1.3 ‰, and δ15N values varied by 6.6 ± 1.1 ‰, respectively. In both regions, the samples identified as being from Pará and Mato Grosso do Sul showed an overlap. In addition, the results fitted with data from the state of Maranhão, in which the values of δ13C and δ15 N were -28.8 ± 1.6 ‰ and 2.9 ± 2.5 ‰, respectively. In the case of cocaine, the present study could not be related to the results from the literature. One possible explanation may be related to the non-purification of ...

Objetivos: o intuito deste trabalho foi definir o intervalo de valores possíveis para cada isótopo de carbono-13 e nitrogênio-15 da cocaína e maconha apreendidas em Botucatu-SP pretendendo-se distinguir a origem geográfica da droga. Materiais e Métodos: amostras de maconha e de cocaína foram recolhidas, no momento de sua incineração. Em seguida, no Centro de Isótopos Estavéis (CIE) da Unesp de Botucatu, as amostras de maconha foram submetidas ao processo de secagem e subsequente moagem. As amostras de cocaína não necessitaram passar pelos processos de secagem e moagem por já apresentarem granulometria adequada. Posteriormente, as amostras de ambas as drogas foram pesadas de acordo com os padrões de pesagem para carbono-13 e nitrogênio-15. Por último, os gases CO2 e N2 das amostras foram obtidos no analisador elementar para serem analisados no espectrômetro de massa em prol da obtenção dos valores de δ13C e e δ15N em ‰. Resultados e Discussão: os resultados da maconha possibilitaram a comparação com regiões de Queensland, Áustrália, de acordo com o intervalo de δ13C entre -29.9‰ e -29.3‰ e o intervalo de δ15N, de 4.1‰ a 5.8‰. Os resultados encontrados também foram condizentes com aqueles do estado do Pará, em que os valores de δ13C e δ15 N foram -30.3 ± 0.7‰ e 5.0 ± 1.3‰, respectivamente, e com aqueles oriundos do estado do Mato Grosso do Sul, nos qual os valores de δ13C variaram em -28.7 ± 1.3‰, e os valores de δ15N variaram em 6.6 ± 1.1‰, respectivamente. Em ambas as regiões, as amostras possivelmente provenientes do Pará e Mato Grosso do Sul exibiram uma sobreposição. Além disso, as amostras se encaixaram com os dados provenientes do estado do Maranhão, no qual os valores de δ13C e δ15 N, -28.8 ± 1.6‰ e 2.9 ± 2.5‰. Já no caso da cocaína, o presente estudo não pôde ser relacionado com os resultados da literatura. Uma possível explicação ...
Keywords: Cocaina; Maconha; Narcóticos; Isótopos estáveis; Cocaine; Cannabis